Cytolytic action of Vibrio vulnificus haemolysin on mast cells from rat peritoneal cavity - Yamanaka, H.; Sugiyama, K.; Furuta, H.; Miyoshi, S.; Shinoda, S. (Journal of Medical Microbiology, 1990)
Summary The mode of action of Vibrio vulnificus haemolysin (VVH) on mast cells from the peritoneal cavity of the rat was examined. VVH induced histamine release, and damage to the mast cells, in a dose-dependent fashion. When 1 μg of VVH was added to c. 105 mast cells at 37°C, histamine release was observed after a lag period of 5-10 s, and was complete within 5 min. The action was temperature-dependent, and was not induced at 4°C. Disodium cromoglycate, a membrane stabiliser for mast cells, inhibited the histamine release significantly, but the effect was not dose-dependent. Moreover, leakage of lactate dehydrogenase from VVH-treated mast cells was observed. These results suggest that VVH acts on the cell membrane of mast cells and is cytolytic.